Multidrug Resistance Proteins and the Renal Elimination of Inorganic Mercury Mediated by 2,3-Dimercaptopropane-1-Sulfonic Acid and Meso-2,3-dimercaptosuccinic Acid - Bridges, Christy C. (2007)
Current therapies for inorganic mercury (Hg(2+)) intoxication include administration of a metal chelator, either 2,3-dimercaptopropane-1-sulfonic acid (DMPS) or meso-2,3-dimercaptosuccinic acid (DMSA). After exposure to either chelator, Hg(2+) is rapidly eliminated from the kidneys and excreted in the urine, presumably as an S-conjugate of DMPS or DMSA. The multidrug resistance protein 2 (Mrp2) has been implicated in this process. We hypothesize that Mrp2 mediates the secretion of DMPS- or DMSA-S-conjugates of Hg(2+) from proximal tubular cells. To test this hypothesis, the disposition of Hg(2+) was examined in control and Mrp2-deficient TR(−) rats. Rats were injected i.v. with 0.5 μmol/kg HgCl(2) containing (203)Hg(2)(+). Twenty-four and 28 h later, rats were injected with saline, DMPS, or DMSA. Tissues were harvested 48 h after HgCl(2) exposure. The renal and hepatic burden of Hg(2+) in the saline-injected TR(−) rats was greater than that of controls. In contrast, the amount of Hg(2+) excreted in urine and feces of TR(−) rats was less than that of controls. DMPS, but not DMSA, significantly reduced the renal and hepatic content of Hg(2+) in both groups of rats, with the greatest reduction in controls. A significant increase in urinary and fecal excretion of Hg(2+), which was greater in the controls, was also observed following DMPS treatment. Experiments utilizing inside-out membrane vesicles expressing MRP2 support these observations by demonstrating that DMPS- and DMSA-S-conjugates of Hg(2+) are transportable substrates of MRP2. Collectively, these data support a role for Mrp2 in the DMPS- and DMSA-mediated elimination of Hg(2+) from the kidney.